Combinational IL-2/IL-15 induction does not further enhance IL-15-induced lymphokine-activated killer cell cytotoxicity against human leukemia/lymphoma cells - Ozdemir, Oner (Clinical immunology (Orlando, Fla.), 2005)
In vitro comparisons of induction of perforin (PFP), granzyme B (GRB), production of cytokines, and cell-mediated cytotoxicity by interleukin-2 (IL-2), interleukin-15 (IL-15), or combinational IL-2/IL-15-induced lymphokine-activated killer cells were studied in this study. Whereas IL-2-induction was associated with a decrease in cultured cell population over a 7-day period, IL-15 alone or in combination with IL-2 resulted in significant increase including cytotoxic T lymphocytes and subsets of CD56+ lymphocytes, particularly cytokine-induced killer and cytolytic natural killer-T lymphocytes. The overall PFP, GRB, and tumor necrosis factor-alpha expression in different subtypes were also significantly higher with IL-15 alone or in combination with IL-2 induction with resultant superior cytotoxicity compared to IL-2 treatment. There was no significant advantage of addition of IL-2 over IL-15 induction. These results offer further information on the cytotoxic potency of these cytokines and their mechanisms of action implicating potential use of IL-15 as part of cytokine adoptive immunotherapy